Design of plasma antenna for reconfigurable beam steering technique / Hajar Ja’afar - Ja’afar, Hajar (Institute of Graduate Studies, UiTM, 2016)
The industrial potential of plasma technology is well known and excellent demonstrated in several processes of microwave technology, which incorporate some use of an ionized medium. In vast majority of approaches, the plasma, or ionized volume, simply replaced a solid conductor. Highly ionized plasma is essentially a good conductor, and therefore plasma filaments can serve as transmission line elements for guiding waves, or antenna surfaces for radiation. Plasma antenna is a kind of antenna that radiate electromagnetic wave (EM) energy based on ionized gas instead of metallic conductor in antenna design. In this research work, the development using plasma medium as a conductor element instead of metal medium is investigated. Three new design antenna by using plasma concepts were proposed; namely cylindrical monopole plasma antenna using electrode-less discharge tube, monopole plasma antenna using fluorescent tube and reconfigurable plasma antenna array. The research described in this project introduces the analysis of cylindrical monopole plasma antenna. Three types of gases with three different pressure which are Argon gas, Neon gas and Hg-Ar gas (mixture of Argon gas and mercury vapor) with pressure at 0.5 Torr, 5 Torr and 15 Torr respectively is used in this research to observe the interaction between plasma medium and radio frequency (RF) signal…